2013
DOI: 10.1186/1748-717x-8-235
|View full text |Cite
|
Sign up to set email alerts
|

Radiation testing of the AeroForm co2-based breast tissue expander implant

Abstract: BackgroundTissue expanders are used in breast reconstruction after mastectomy to stretch the remaining tissue to create space for placement of permanent breast implants. The AeroForm™ Tissue Expander, developed by AirXpanders™ Inc., contains electronic components designed to activate the release of carbon dioxide from an internal reservoir to inflate the expander. Breast cancer patients who undergo mastectomy and tissue expander/implant-based breast reconstruction may require radiation therapy at doses up to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…However, several articles have now been published which document that radiation therapy can be safely administered while the carbon dioxide-based devices are still in patients. 13,14 In the American AirXpanders Patient Activated Controlled Tissue Expander trial, the device has been used only in patients who met a specific set of inclusion and exclusion criteria, namely, excluding smokers, patients with a body mass index over 33, patients younger than 18 or older than 70 years, and patients who must fly during the expansion process. In the future, it will also be helpful to evaluate the safety and efficacy in those patients with a higher risk of developing breast reconstruction complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, several articles have now been published which document that radiation therapy can be safely administered while the carbon dioxide-based devices are still in patients. 13,14 In the American AirXpanders Patient Activated Controlled Tissue Expander trial, the device has been used only in patients who met a specific set of inclusion and exclusion criteria, namely, excluding smokers, patients with a body mass index over 33, patients younger than 18 or older than 70 years, and patients who must fly during the expansion process. In the future, it will also be helpful to evaluate the safety and efficacy in those patients with a higher risk of developing breast reconstruction complications.…”
Section: Discussionmentioning
confidence: 99%
“…A new tissue expander system, the AeroForm™ (AirXpanders®, Palo Alto, CA), has recently become available to patients 6–9 . Aeroform expander consists of an implantable silicone tissue expander containing a metal reservoir of compressed carbon dioxide.…”
Section: Introductionmentioning
confidence: 99%
“…Aeroform expander consists of an implantable silicone tissue expander containing a metal reservoir of compressed carbon dioxide. The metallic reservoir causes a significant attenuation and inhomogeneous doses around the expander in PMRT 9–12 with 60 Co and 6MV. Moni 10 has shown that the treatment planning system (TPS) can have significant dose error (>5%) at the chest wall–expander interface.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, use of air in tissue expanders (rather than saline) or self-expanding expanders filled with CO 2 has begun to be incorporated into clinical practice; initial clinical data have been promising, and prospective data have demonstrated the safety and feasibility of the technique. [11][12][13][14] However, there is a paucity of data documenting the safety and efficacy of such reconstructions in patients undergoing radiation therapy. [14][15][16] Why is this significant?…”
mentioning
confidence: 99%
“…[11][12][13][14] However, there is a paucity of data documenting the safety and efficacy of such reconstructions in patients undergoing radiation therapy. [14][15][16] Why is this significant? Air has very different properties compared with saline, which is similar to tissue with respect to radiation interactions.…”
mentioning
confidence: 99%